Correlation of Near-Infrared (Nir) Spectroscopy with Water Quality Sensors to Detect Concentration of Saccharomyces Boulardii in Water - Muhammad Aqil, Hafizzan Nordin; Mohd Faizal, Jamlos; Siti Anis Dalila, Muhammad Zahir; Mas Ira Syafila, Mohd Hilmi Tan; Hajar Fauzan, Ahmad; Mohd Aminudin, Jamlos; Nor Husna, Mat Hussin (Elsevier, 2023)
Terahertz (THz) sensing of high sensitivity detection has given the possibility of a non-invasive method for measuring and monitoring microorganism from water resources. The purpose of this study is to analyse the effectiveness of Near-infrared (NIR) spectroscopy as a non-destructive and in-situ measurement-based method for detection of Saccharomyces boulardii (S. boulardii) in water. Samplings are prepared in biotechnology lab in Universiti Malaysia Pahang (UMP), a yeast species of S. boulardii is used as a model microorganism. A single colony of yeast was inoculated in liquid broth media and incubated for overnight culture. A standard serial dilution method was applied to prepare five samples at different yeast concentration in corresponding test tubes of 0%, 10%, 20%, 50% and 100%. A hand-held NIR spectroscopy with range from 900nm to 1700nm wavelength is deployed gapless to scan those test tubes through its optical window. Meanwhile another sample with similar concentrations are inoculated into volume 0.0071 m3 of water equipped with water quality sensor system for monitoring and analysis purpose. The findings show inoculation certain concentration of 10%, 20%, 50% and 100% of S. boulardii into the water generated certain level of NIR spectroscopy’s spectral absorbance of 0.723, 0.64, 0.357 and 0.121 correspondingly at 1067 nm wavelength. This proves NIR spectroscopy is a highly-sensitivity THz sensor at 1067 nm wavelength as absorbance is at the minimum level as S. boulardii concentration is at the maximum. This finding is further validated by Dissolved Oxygen (DO) sensor which demonstrates rising maximum of 8 ppm after an hour of S. boulardii’s inoculation compared to 4 ppm in a normal water. However, the DO level back to normal after 5 hours due to the acclimatization process of the yeast and demonstrate capability of DO sensor to detect presence of yeast in water. PCA and PLS analysis based NIR spectroscopy’s spectral absorbance also demonstrates ability to categorise severity of a microbial illness depending on its concentration. The results from this study has suggested that the NIR spectroscopy sensor as an excellent option for microbial sensing in water.